Perancangan Pembuatan Aplikasi Rental Kendaraan Berbasis Website - Irwanto; Annisa Aulia Yulianti; Arip Solehudin; Apriade Voutama (STEKOM PRESS, 2022)
Technology is a means of information which is very important for a company. information is expected to facilitate work to achieve goals optimal. With the increasing popularity of the internet, many business fields, especially those held large already provides online services. An example is a car rental business with take advantage of website services that contain information and the order is expected to be promotional media and will expedite the process booking. The research method used in build a car rental booking application with PHP and MySQL based website service is by analyzing needs, system design, database design, and design dialog screen.